2019
DOI: 10.3319/tao.2018.12.16.01
|View full text |Cite
|
Sign up to set email alerts
|

The roles of vertical wind shear and topography in formation of convective asymmetries in Typhoon Nanmadol (2011)

Abstract: The effects of terrain and environmental vertical wind shear on the intensity, structure, and asymmetric convection of Typhoon Nanmadol (2011) were investigated using a high-resolution numerical model. Terrain-removed sensitivity experiments were conducted to elucidate the relative role of terrain in the formation of the storm's asymmetric convection. Several sensitivity experiments were also employed to examine whether convective asymmetry formed in the simulated storm was influenced by model physics or exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…TC motion was calculated using the longitude and latitude after interpolation of hourly TC centers from the JTWC best track. For VWS, wind field data from the analysis field of the National Centers for Environmental Prediction (NCEP) Final Analysis (FNL) were used to calculate wind vector differences between 200 and 850 hPa and were averaged within an annulus extending 28-88 from the storm's center (Chou et al 2019). To evaluate the degree of confidence of calculation results of VWS from NCEP-FNL, the VWS data were further compared with those from the Statistical Hurricane Intensity Prediction Scheme (SHIPS) where wind data over the 200-800 km annulus were calculated.…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…TC motion was calculated using the longitude and latitude after interpolation of hourly TC centers from the JTWC best track. For VWS, wind field data from the analysis field of the National Centers for Environmental Prediction (NCEP) Final Analysis (FNL) were used to calculate wind vector differences between 200 and 850 hPa and were averaged within an annulus extending 28-88 from the storm's center (Chou et al 2019). To evaluate the degree of confidence of calculation results of VWS from NCEP-FNL, the VWS data were further compared with those from the Statistical Hurricane Intensity Prediction Scheme (SHIPS) where wind data over the 200-800 km annulus were calculated.…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…Although the storm motion is traditionally considered to be the primary factor that contributes to the TC structural asymmetry, its effect is significantly weaker than the influence of vertical wind shear on TC convection, based on lightning data in TCs [10]. Recent studies have shown that large environmental vertical wind shear can induce strong asymmetric structures observed in hurricanes and typhoons [11,12]. Moreover, two kinds of rain-rate data have been used to investigate TC rainfall asymmetry; these data show that precipitation asymmetry is much more associated with wind shear than storm motion [13].…”
Section: Introductionmentioning
confidence: 99%